Bioinformatics study of GATA family in Amaranthus hypochondriacus: Identification, Characterization, and Expression Profiles: Investigation of the GATA family in grain amaranth at the genome-wide scale - Vu, Xuan Duong; Le, Man Thi; Le, Quynh Thi Ngoc; Chu, Ha Duc; La, Hong Viet; Huy Gioi, Dong; Tran, Huyen Thi Thanh; Cao, Phi Bang (Journal of Tropical Life Science, 2025)
GATA transcription factors (TFs) play critical roles in regulating various physiological and biochemical processes in plants. However, their functions in grain amaranth (Amaranthus hypochondriacus) remain unexplored. This study identified and characterized 23 GATA TFs (AhGATAs) in grain amaranth through genome-wide bioinformatics analysis. The gene structure, gene duplication, phylogenetic analysis, and protein features were performed. As a result, the AhGATA TF family in grain amaranth exhibited diverse gene structures, including variations in exon-intron organization, with the number of exons ranging from one to eleven. We also found that the AhGATA TF family in grain amaranth could be grouped into four different clades as similar to other higher plant species. Next, the recent RNA-Seq dataset was explored to re-analyze the transcriptional changes of the AhGATA genes in several main organs during the growth and development of grain amaranth plants. We proposed four AhGATA genes, including AhGATA01, 05, 13, and 19, which were exclusively expressed in at least one major organ, such as stems, roots, leaves, maturing seeds, flowers, immature seeds, and green cotyledons. In summary, this current study could provide the basis for further exploration of the GATA gene family functions in plants and enhance our understanding of cellular regulation in plant defense mechanisms.